The Therapeutic Effects of Viparita Karani Mudra on Non-Communicable Diseases - Nidhi; singh, Jai Prakash; antiwal, Meera; kumar maurya, Pranshu (International Research Journal of Ayurveda & Yoga, 2025)
Objective: To explore the physiological and energetic effects of inverted yogic posture – Viparita Karani Mudra in managing non-communicable diseases (NCDs). Methods: A review of classical yogic texts (Hatha Yoga Pradipika, Gheranda Samhita) combined with an analysis of recent scientific literature was conducted to assess the impact of these asanas on various body systems. Observations: These postures enhance circulation, stimulate the hypothalamic-pituitary axis, regulate thyroid and autonomic nervous systems, and promote upward movement of Pranic energy. Clinical studies report reduced stress, improved immunity, and balanced cardiovascular parameters. Discussion: Viparita Karani integrates physical and energetic mechanisms, activating chakras and facilitating parasympathetic dominance, thus supporting holistic health. Precautions are necessary for those with cervical or ocular vulnerabilities. Conclusion: Inverted asanas serve as safe, complementary interventions in NCD management by harmonizing body, mind, and energy systems and augmenting conventional treatments.